USE OF THE GENERAL ARRIVAL DECLARATION: RESPONSIBLE ENTITIES - YAKOVENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to certain aspects of submitting and applying the General declaration of arrival in Ukraine. The effectiveness of prior information depends on the defined circle of persons who can submit the General declaration of arrival and are responsible for it. The work presents the international experience of delineating the persons responsible for the submission of the general declaration of arrival. Common in different countries is the permission to submit a general declaration to persons other than the carrier who can present the cargo to the customs authority. At the same time, the responsibility for submission rests with the carrier. Recent changes in the customs legislation of Ukraine significantly expanded the list of persons who can submit a general declaration of arrival. At the same time, in contrast to international practice, Ukrainian legislation does not take into account such aspects as the need to agree on the submission of the PDP by all participants; the availability of all necessary information to the persons submitting the LDP; the possibility of an additional request from the customs authorities for additional information, which all participants must provide and be responsible for providing it. Legislative innovations also concern the conceptual apparatus. Thus, such characteristics as the importance of meeting the deadlines and the order of its submission were added to the definition of the general declaration of arrival. In addition, the term "carrier" has undergone changes, which led to the appearance of inconsistencies between European and Ukrainian legislation regarding the person responsible for submitting the LDP in case of combined transportation. The results of the study emphasized the need to introduce responsibility for non-submission, untimely submission of a tax return, or submission of incomplete or inaccurate information. It is also advisable to develop a mechanism of responsibility for all participants in the supply chain. This involves consideration for risk assessment separately for each participant. Thus, each of the participants will be interested in providing the carrier with information about each shipment.